2024
DOI: 10.1039/d3qo01865b
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed electrolysis: enhancing primary benzylic C(sp3)–H nucleophilic fluorination

Alexander P. Atkins,
Atul K. Chaturvedi,
Joseph A. Tate
et al.

Abstract: Pulsed electrolysis waveforms benefit primary benzylic cation generation and fluorination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…In 2024, Lennox and co-workers reported their investigation in exploring how alternative electrolysis waveforms might assist in the generation of reactive primary benzylic cations for nucleophilic fluorination ( Figure 43 ) [ 104 ]. The challenge involved avoiding over-oxidation of the monofluorination product and overcoming mass transportation issues.…”
Section: Reviewmentioning
confidence: 99%
“…In 2024, Lennox and co-workers reported their investigation in exploring how alternative electrolysis waveforms might assist in the generation of reactive primary benzylic cations for nucleophilic fluorination ( Figure 43 ) [ 104 ]. The challenge involved avoiding over-oxidation of the monofluorination product and overcoming mass transportation issues.…”
Section: Reviewmentioning
confidence: 99%
“…These advancements have led to improved selectivity in chemical processes [36][37][38] and/or the preservation of electrode surfaces to prevent passivation. [39,40] Using Pt plates as electrodes, we performed pulsed electrosynthesis by investigating the effect of frequency (Hz) on the reaction (Figure 2F). We found that 0.2 Hz was the ideal frequency for the model substrate with up to 2.5-fold increase in yield.…”
mentioning
confidence: 99%